The Urgency of Establishing an Electoral Judicial Institution as an Effort to Strengthen the Electoral System in Indonesia - Wicitra, Made Widyarini Kusuma; Wijayanto, Wijayanto; Herawati, Nunik Retno (PERSPEKTIF, 2024)
Periodically, every five years, general elections are held as a form of democracy in Indonesia. During elections, political issues are often followed by controversies, conflicts, and disputes in local power competitions. These issues include cheating, money politics, and vote manipulation. The purpose of this study is to encourage the establishment of a permanent electoral court in the constitutional system and in the form of a state institution to handle any existing election results disputes, whether for the presidential election, legislative election, or regional election. To achieve the electoral justice system's legal certainty and utility principles. The research method was used qualitatively with a case study research design. The results indicate that the establishment of an election court institution is essential, considering elections are held regularly and periodically as part of people's sovereignty representation and efforts to establish a fair electoral system. An election court institution is necessary for Indonesian elections, tasked with handling every election dispute, thereby allowing the Constitutional Court to focus solely on testing laws against the 1945 Constitution. This journal concludes that an electoral justice institution needs to be established permanently, with competent judges and resources to handle every election-related case to realize an electoral justice system.